Primary PCI-A Real Life Challenge in Bangladesh - Zaman, S M Mustafa (Bangladesh Journal of Medicine, 2024)
Primary percutaneous coronary intervention (PPCI) stands as a cornerstone in the management of acute coronary syndrome, offering significant mortality benefits when promptly administered. Despite the proven efficacy of Primary PCI, its utilization rate in Bangladesh remains alarmingly low, averaging merely 4-6%. However, its implementation in Bangladesh faces multifaceted challenges reflective of the country’s healthcare landscape. Different studies explore the real-life challenges encountered in delivering PPCI in Bangladesh, where access to specialized PPCI center is limited, health insurance coverage is deficient, public awareness regarding the criticality of timely intervention remains inadequate, delayed hospital presentation due to hesitancy and congested urban traffic exacerbating pre-hospital delays were assessed. Addressing these challenges requires a multifaceted approach involving healthcare policy reforms, establishment of more PPCI-capable centers, expansion of health insurance coverage, and extensive public health campaigns aimed at raising awareness about the significance of timely intervention in acute coronary events. By mitigating these barriers, Bangladesh can enhance the accessibility and utilization of PPCI services, ultimately improving outcomes for patients afflicted with acute coronary syndrome. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 135-136